Patient-Level Costing, Strategic Reimbursement, and Budget-Constrained Coverage in Rare Diseases: A TDABC-Based Analysis of Severe Haemophilia A - Tânia Saraiva; Tiago José Leite Cardoso (Games, 2026)
Rare-disease treatment financing is challenging because high-cost therapies, clinical need, and budget constraints create interdependent decisions among manufacturers, public payers, and healthcare providers. This article combines patient-level time-driven activity-based costing (TDABC) with a sequential reimbursement benchmark and a fixed-budget coverage analysis for severe haemophilia A. Using institutional pathway data and a representative clinical profile, the study estimates an annual treatment cost of EUR 105,429.14 for the representative patient, of which EUR 98,514.04, or 93.4%, corresponds to pharmaceutical expenditure. TDABC is used to identify the clinical and operational resources consumed throughout the treatment pathway and the practical capacity allocated to its delivery. The analytical model then translates the resulting cost structure into reimbursement, provider-adoption, and population-coverage conditions. The results show that treatment feasibility and budget-constrained coverage are driven primarily by drug price, body weight, dose intensity, and administration frequency, while non-drug operational costs have a comparatively limited effect. The article contributes by connecting institution-specific patient-level costing with the interdependent implications of treatment cost for manufacturers, payers, providers, and patient access. The framework provides a transparent reimbursement benchmark rather than a complete bargaining model and supports affordability, budget-impact, and treatment-capacity assessments in rare diseases.